Canadian Registry of Electronic Device Outcomes: remote monitoring outcomes in the Abbott battery performance alert—a multicentre cohort. Issue 8 (20th February 2021) - Kumar, Sharath; Davis, Jason; Thibault, Bernard; Mangat, Iqwal; Coutu, Benoit; Bennett, Matthew; Philippon, Francois; Sandhu, Roopinder; Sterns, Laurence; Essebag, Vidal; Nery, Pablo; Wells, George; et al.
Abstract: Aims: Cardiac implantable electronic devices with device advisories have the potential of device malfunction. Remote monitoring (RM) of devices has been suggested to allow the identification of abnormal device performance and permit early intervention. We sought to describe the outcomes of patients with and without RM in devices subject to the Abbott Premature Battery Depletion (PBD) advisory with data from a Canadian registry. Methods and results: Patients with an Abbott device subject to the PBD advisory from nine implantable cardioverter defibrillator (ICD) implanting centres in Canada were included in the registry. The use of RM was identified from baseline and follow-up data in the registry. The primary outcome was detection of PBD and all-cause mortality. A total of 2666 patients were identified with a device subject to the advisory. In all, 1687 patients (63.2%) had RM at baseline. There were 487 deaths during follow-up. At a mean follow-up of 5.7 ± 0.7 years, mortality was higher in those without a remote monitor compared with RM at baseline (24.7% vs. 14.5%; P < 0.001). Pre-mature battery depletion was identified in 36 patients (2.1%) with RM vs. 7 (0.7%) without RM ( P = 0.004). Time to battery replacement was significantly reduced in patients on RM (median 5 vs. 13 days, P = 0.001). Conclusion: The use of RM in patients with ICD and cardiac resynchronization therapy under advisory improved detection of PBD, time to device replacement, and was associated with a reduction in all-cause mortality. The factors influencing the association with mortality are unknown and deserve further study.